BEAUTY MYTH AND FEMALE RESISTANCE IN THE MOVIE I FEEL PRETTY - SISWANTIA SAR; WITA DWI PAYANA; RAHIL HELMI (State University of Medan, 2023)
This paper aims to describe the beauty myth and the female resistance in the movie I Feel Pretty. This research uses gender study which focuses on beauty myth and the female resistance towards the beauty myth. The object material in this study is a chick lit movie, I Feel Pretty. The formal object of this research is gender study that focuses on beauty myth. Data analysis was performed through qualitative descriptive techniques by interpreting the data found in the movie I Feel Pretty and linked to beauty myth theories. Beauty myth has been promoted through the mass media, including the movie I Feel Pretty. However, there are also various forms of resistance performed by the female character to challenge the beauty myth and promote a more inclusive and diverse definition of beauty. This paper tries to highlight some resistances towards beauty myth in this movie, which are being confident, being passionate, and having a good personality. This research eventually finds out that having these traits is a form of resistance against the normalized unreasonable beauty standard.